2021
DOI: 10.1155/2021/5539376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Technological Process on True Retention Rate of Eicosapentaenoic and Docosahexaenoic Acids, Lipid Oxidation and Physical Properties of Canned Smoked Sprat (Sprattus sprattus)

Abstract: In connection with the severe deficiencies of EPA and DHA in the human diet, the industry should provide inexpensive fish products that are characterized by the appropriate lipid quality. The influence of the technological process on true retention rate of EPA and DHA, indicators of lipid oxidation and physical properties, of canned smoked sprat in oil was investigated. It was assumed that the double dose of heat during the technological process (smoking/sterilization) can significantly affect the quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…During the smoking process, both hot and cold, a decrease in the content of EPA and DHA acids was observed, especially significantly in the case of hot smoking. A reduction in lipid content, especially EPA and DHA, was observed by Domiszewski and Mierzejewska [ 47 ] studying the effect of processing on the actual retention of eicosapentaenoic and docosahexaenoic acid, lipid oxidation, and physical properties of canned smoked sprat ( Sprattus sprattus ). The kinetics of lipid quality changes in salmon during thermal processing was also described by Kong et al [ 48 ].…”
Section: Resultsmentioning
confidence: 97%
“…During the smoking process, both hot and cold, a decrease in the content of EPA and DHA acids was observed, especially significantly in the case of hot smoking. A reduction in lipid content, especially EPA and DHA, was observed by Domiszewski and Mierzejewska [ 47 ] studying the effect of processing on the actual retention of eicosapentaenoic and docosahexaenoic acid, lipid oxidation, and physical properties of canned smoked sprat ( Sprattus sprattus ). The kinetics of lipid quality changes in salmon during thermal processing was also described by Kong et al [ 48 ].…”
Section: Resultsmentioning
confidence: 97%
“…High temperature could induce free radical generation, followed by secondary oxidized lipid products. The rate of decreasing PUFA depended on the heating profile [ 33 ]. In this study, 30% loss of EPA was found after heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a previous study in critical patients found no associations between receiving hyperosmolar nutrition and medication via nasogastric tube, and feeding intolerance, diarrhea, constipation, gastric residual volume, nausea, and vomiting [ 34 ]. However, an increased risk of diarrhea was found to be associated with hyperosmolar medication via the naso-duodenal route (OR 138.7 (95% CI: 2.33; 8245)) [ 33 ]. Therefore, further evaluation in clinical setting research is needed to monitor this product for possible complications.…”
Section: Discussionmentioning
confidence: 99%